«ADMINISTRATIVE ACTIVITY»: ESSENCE, CONTENT AND MEANING IN THE SUBJECT OF ADMINISTRATIVE LAW - Kunev, Yuriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article: determine the essence, content and meaning in the subject of administrative law of such an administrative-legal concept as «administrative activity». Research methods: systematic analysis and synthesis, doctrinal knowledge of the theory of administrative law; methods of dialectical and formal logic made it possible to formulate and clarify the main concepts of administrative activity, as well as a method of generalization and modeling of new theoretical knowledge. Results: identified problems of further development of the concept and system of administrative activity. A system of activities, components of the public administration system, is presented. Policy in the administrative sphere is formalized in the norms of administrative legislation and is implemented in administrative activity, primarily as an activity of legal interaction between subjects of private and public law. The application of the concept of «administrative activity» creates a unity of approach to its legal regulation by the norms of substantive and formal administrative law. The foreign experience and approach to the development of the public administration system is based on the foundation of a clearly verified and stable legal system, which ensures the rights and legitimate interests of citizens at the minimum necessary level by legal means. The introduction of the concept of «public administration», which absorbs the concept of «administrative activity» in the theory of administrative law of Ukraine, takes place unsystematically, in the absence of an understanding of its meaning, content and place in the system of administrative and legal concepts. Discussion: the proposition that the legal component of public administration is characterized by the basic concepts of «administrative law», «administrative activity», «administrative legislation» is argued. A definition of the concepts «administrative activity» and «public-administrative activity» is proposed.